N-terminal pro-B-type natriuretic peptide and microsize myocardial infarction risk in the reasons for geographic and racial differences in stroke study - Madeline R. Sterling; Raegan W. Durant; Joanna Bryan; Emily B. Levitan; Todd M. Brown; Yulia Khodneva; Stephen P. Glasser; Joshua S. Richman; George Howard; Mary Cushman; Monika M. Safford (BMC Cardiovascular Disorders, 2018)
Abstract Background N-terminal pro B-type peptide (NT-proBNP) has been associated with risk of myocardial infarction (MI), but less is known about the relationship between NT-proBNP and very small non ST-elevation MI, also known as microsize MI. These events are now routinely detectable with modern troponin assays and are emerging as a large proportion of all MI. Here, we sought to compare the association of NT-proBNP with risk of incident typical MI and microsize MI in the REasons for Geographic and Racial Differences in Stroke (REGARDS) Study. Methods The REGARDS Study is a national cohort of 30,239 US community-dwelling black and white adults aged ≥ 45 years recruited from 2003 to 2007. Expert-adjudicated outcomes included incident typical MI (definite/probable MI with peak troponin ≥ 0.5 μg/L), incident microsize MI (definite/probable MI with peak troponin < 0.5 μg/L), and incident fatal CHD. Using a case-cohort design, we estimated the hazard ratio of the outcomes as a function of baseline NT-proBNP. Competing risk analyses tested whether the associations of NT-proBNP differed between the risk of incident microsize MI and incident typical MI as well as if the association of NT-proBNP differed between incident non-fatal microsize MI and incident non-fatal typical MI, while accounting for incident fatal coronary heart disease (CHD) as well as heart failure (HF). Results Over a median of 5 years of follow-up, there were 315 typical MI, 139 microsize MI, and 195 incident fatal CHD. NT-proBNP was independently and strongly associated with all CHD endpoints, with significantly greater risk observed for incident microsize MI, even after removing individuals with suspected HF prior to or coincident with their incident CHD event. Conclusion NT-proBNP is associated with all MIs, but is a more powerful risk factor for microsize than typical MI.